DUE PROCESS OF LAW DALAM PENANGGULANGAN TINDAK PIDANA DI INDONESIA - Fernando, Zico Junius (Universitas Prof. Dr. Hazairin, SH, 2021)
In the criminal justice system, due process of law is defined as a legal process that is good, true and fair. Such legal process occurs, when law enforcement officers related to the process, not only carry out their duties in accordance with existing rules, but also implement the principles and principles which underlie a fair legal process. Implementation of Due Process Of Law is indispensable in maintaining human rights are protected, is associated with its own criminal law issues, protection of witnesses and victims of crime as well as the role of the community towards the protection of victim.